Association Between Oral Anticoagulant Adherence and Serious Clinical Outcomes in Patients With Atrial Fibrillation: A Long‐Term Retrospective Cohort Study - Abdollah Safari; Hamed Helisaz; Shahrzad Salmasi; Adenike Adelakun; Mary A. De Vera; Jason G. Andrade; Marc W. Deyell; Peter Loewen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Patients with atrial fibrillation are frequently nonadherent to oral anticoagulants (OACs) prescribed for stroke and systemic embolism (SSE) prevention. We quantified the relationship between OAC adherence and atrial fibrillation clinical outcomes using methods not previously applied to this problem. Methods and Results Retrospective observational cohort study of incident cases of atrial fibrillation from population‐based administrative data over 23 years. The exposure of interest was proportion of days covered during 90 days before an event or end of follow‐up. Cox proportional hazard models were used to evaluate time to first SSE and the composite of SSE, transient ischemic attack, or death and several secondary outcomes. A total of 44 172 patients were included with median follow‐up of 6.7 years. For direct OACs (DOACs), each 10% decrease in adherence was associated with a 14% increased hazard of SSE and 5% increased hazard of SSE, transient ischemic attack, or death. For vitamin K antagonist (VKA) the corresponding increase in SSE hazard was 3%. Receiving DOAC or VKA was associated with primary outcome hazard reduction across most the proportion of days covered spectrum. Differences between VKA and DOAC were statistically significant for all efficacy outcomes and at most adherence levels. Conclusions Even small reductions in OAC adherence in patients with atrial fibrillation were associated with significant increases in risk of stroke, with greater magnitudes for DOAC than VKA. DOAC recipients may be more vulnerable than VKA recipients to increased risk of stroke and death even with small reductions in adherence. The worsening efficacy outcomes associated with decreasing adherence occurred without the benefit of major bleeding reduction.